Association of Sequential Organ Failure Assessment (SOFA) components with mortality. Issue 6 (10th April 2022) - Pölkki, Anssi; Pekkarinen, Pirkka T.; Takala, Jukka; Selander, Tuomas; Reinikainen, Matti
Abstract: Background: Sequential Organ Failure Assessment (SOFA) is a practical method to describe and quantify the presence and severity of organ system dysfunctions and failures. Some proposals suggest that SOFA could be employed as an endpoint in trials. To justify this, all SOFA component scores should reflect organ dysfunctions of comparable severity. We aimed to investigate whether the associations of different SOFA components with in‐hospital mortality are comparable. Methods: We performed a study based on nationwide register data on adult patients admitted to 26 Finnish intensive care units (ICUs) during 2012−2015. We determined the SOFA score as the maximum score in the first 24 hours after ICU admission. We defined organ failure (OF) as an organ‐specific SOFA score of three or higher. We evaluated the association of different SOFA component scores with mortality. Results: Our study population comprised 63, 756 ICU patients. Overall hospital mortality was 10.7%. In‐hospital mortality was 22.5% for patients with respiratory failure, 34.8% for those with coagulation failure, 40.1% for those with hepatic failure, 14.9% for those with cardiovascular failure, 26.9% for those with neurologic failure and 34.6% for the patients with renal failure. Among patients with comparable total SOFA scores, the risk of death was lower in patients with cardiovascular OF compared with patients with other OFs. Conclusions: All SOFA components are associated with mortality, but their weights are not comparable. High scores of other organ systems mean a higher risk of death than high cardiovascular scores. The scoring of cardiovascular dysfunction needs to be updated.